Performance of synthetic storm technique in estimating fade dynamics in equatorial Malaysia - Jong, Siat Ling; Riva, Carlo G.; D'Amico, Michele; Lam, Hong Yin; Mohamed Yunus, Mawarni; Din, Jafri (John Wiley and Sons Ltd., 2018)
In this paper, the synthetic storm technique (SST) is applied to 1-minute rainfall rate collected from a rain gauge to predict the fade dynamics of the signal in an earth-to-satellite link in an equatorial climate location without the needs of satellite beacon measurements. The obtained results are compared with the statistics calculated from measured rain attenuation and with the ITU recommendation model. As for fade duration, a good agreement with measurements has been found together with a significant improvement in terms of prediction errors with respect to the ITU-R model. Synthetic storm technique is also able to predict fade slope statistics fairly well and has equivalent performance of ITU-R model.